2021
DOI: 10.3390/polym13224000
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Polyvinyl Alcohol−Alginate/Bentonite Semi-Interpenetrating Polymer Network Nanocomposite Hydrogel Beads as an Efficient Adsorbent for the Removal of Methylene Blue from Aqueous Solution

Abstract: Hazardous chemicals like toxic organic dyes are very harmful to the environment and their removal is quite challenging. Therefore there is a necessity to develop techniques, which are environment friendly, cost-effective and easily available in nature for water purification and remediation. The present research work is focused on the development` and characterization of the ecofriendly semi-interpenetrating polymer network (semi-IPN) nanocomposite hydrogels composed of polyvinyl alcohol (PVA) and alginate (Alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…[ 39 ]. In addition, the strong intensity peak at 1180.54 cm −1 (C−OH stretching of secondary alcohol) of PVA was shifted to a low intensity peak at 1080.54 cm −1 in SN2 and 1086.60 cm −1 in SN6, which might indicate the interaction of the −OH of PVA with the C=O of alginate via H-bond ( Figure 11 ) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 ]. In addition, the strong intensity peak at 1180.54 cm −1 (C−OH stretching of secondary alcohol) of PVA was shifted to a low intensity peak at 1080.54 cm −1 in SN2 and 1086.60 cm −1 in SN6, which might indicate the interaction of the −OH of PVA with the C=O of alginate via H-bond ( Figure 11 ) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…[39]. In addition, the strong intensity peak at 1180.54 cm −1 (C−OH stretching of secondary alcohol) of PVA was shifted to a low intensity peak at 1080.54 cm −1 in SN2 and 1086.60 cm −1 in SN6, which might indicate the interaction of the −OH of PVA with the C=O of alginate via H-bond (Figure 11) [42]. A previous study reported that interactions between alginate and anthocyanin molecules occurred via charge-charge interaction between the negatively charged carboxylic groups of the polymeric backbone of alginate and the flavylium cation of anthocyanin [43].…”
Section: Ft-ir Spectroscopymentioning
confidence: 97%
“…It has numerous applications in the textile, tannery, plastics, food, cosmetics, and paper industries. It is also used in the pharmaceutical industry and medical practice (methaemoglobinemia treatment, cyanide poisoning treatment, or as a staining agent) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. But this dye can also cause various negative effects on human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In order to remove the dyes (including methylene blue) from aqueous solutions, several different techniques have been applied as follows: coagulation, flocculation, precipitation, membrane processes, chemical oxidation, electrochemical processes, catalytic reduction, photocatalytic degradation, ion exchange, adsorption, microorganism degradation, membrane bioreactors, aerobic, and anaerobic biological treatments [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation